KORELASI ANTARA BUDAYA ORGANISASI, KEPEMIMPINAN KEPALA SEKOLAH, DAN KINERJA GURU DENGAN PENINGKATAN MUTU PENDIDIKAN PADA SEKOLAH DASAR NEGERI DI KECAMATAN DRAMAGA KABUPATEN BOGOR - Aryanih, Siti; Pujilestari, Yulita; Masriah, Imas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of improving educational quality, a process influenced by various internal school factors, including organizational culture, principal leadership, and teacher performance. The study aims to determine the relationship of organizational culture, principal leadership, and teacher performance with the improvement of educational quality both individually and simultaneously in public elementary schools within the Dramaga District, Bogor Regency. A quantitative approach utilizing a correlational survey method was employed. The study population consisted of 142 teachers, with a sample of 105 teachers determined using Slovin's formula. Data were collected via questionnaires and analyzed using descriptive and inferential statistics, including tests for normality, homogeneity, Pearson correlation, and multiple correlation. The results indicate that organizational culture has a positive and significant relationship with educational quality (r = 0.661; p < 0.05), principal leadership has a positive and significant relationship with educational quality (r = 0.596; p < 0.05), and teacher performance has a positive and significant relationship with educational quality (r = 0.705; p < 0.05). Simultaneously, organizational culture, principal leadership, and teacher performance exhibit a positive and significant relationship with educational quality, with a multiple correlation coefficient of 0.754 and a coefficient of determination of 0.555. These findings demonstrate that improving educational quality requires synergy among a strong organizational culture, effective principal leadership, and professional teacher performance.